Strategic planning in the sphere of education in regions - E. N. Koshkina; I. E. Bocharova; E. R. Orlova; S. A. Bannikov (Вестник университета)
The article is devoted to problems of strategic planning in education. Special attention is paid to the formation of regional education development programs. The article considers the main provisions of the strategic program for the development of the education system at the municipal level as a key position for the formation of a unified educational space. The authors’ analysis of such programs has shown that such programs are often devoid of consistency and are not consistent with the development programs of the leading branches of knowledge and the economy of the region. Based on the legal framework, scientific articles, and the experience of the regions the authors propose a model for the formation of regional strategic planning documents in the field of education, based on the principle of a triple helix of interaction between the state, educational organizations and business. The educational space planned according to this model will differ not only in a new organizational format designed to coordinate the path of education and training, but will also serve as a consolidation of resources from all three sources.